PENGELOLAAN MEDIA SOSIAL INSTAGRAM HUMAS KPKNL BEKASI DALAM MEMBANGUN CITRA INSTITUSI - Saputro, Akbar (FISIP UPNVJ, 2023)
The growing importance of social media for information dissemination advice has changed the way information is disseminated and utilized. The use of social media has become a huge phenomenon in this digital age, where platforms such as Instagram have become one of the most influential and popular communication tools to build and strengthen the image of institutions in the eyes of the public. In the context of organizations, the use of social media is very important to build a positive image and closer interaction with the community, information is spread quickly. This study aims to determine the Management of Instagram Social Media Public Relations of KPKNL Bekasi in Building the Institution's Image. This research uses a qualitative descriptive method where interview data is processed using textual analysis from the informant's point of view through interpretation of meaning. The results showed that the Bekasi State Wealth and Auction Service Office, only uses Instagram and the website as a public relations publication media, KPKNL Bekasi public relations and this can be said that the public relations of KPKNL Bekasi in carrying out its public relations function has not run optimally because it only uses Instagram social media as the main force in public relations publications through social media. Keywords: Instagram, Institutional image, Organization, Public Relations, Social Media.